2015
DOI: 10.14411/eje.2015.079
|View full text |Cite
|
Sign up to set email alerts
|

New set of microsatellite markers for the spotted-wing Drosophila suzukii (Diptera: Drosophilidae): A promising molecular tool for inferring the invasion history of this major insect pest

Abstract: abstract. Historical and observational data for invasive species are often sparse and incomplete, so molecular genetic markers are increasingly used and have proved to be efficient tools to make inferences about invasion histories. Here, we report the development of 28 polymorphic microsatellite markers in the invasive spotted-wing drosophila, Drosophila suzukii (Matsumura, 1931) (Diptera: Drosophilidae) designed from recent genomics resources, and their cross-amplification in closely related Drosophila specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
(13 reference statements)
1
22
0
Order By: Relevance
“…Throughout the course of the invasion of D. suzukii , its genetic diversity changed through bottlenecks and admixture events (Fraimout et al., ). A comparison of the host genotype across neutral markers (6–28 microsatellites) and six X‐linked loci in coding and noncoding sequences indicated relatively high intraspecific genetic variation within and between populations in the invaded regions (Adrion et al., ; Bahder, Bahder, Hamby, Walsh, & Zalom, ; Fraimout et al., , ). It is therefore reasonable to assume that there is substantial intraspecific genotypic variation in the invaded populations that can contribute to the variable D. suzukii –parasitoid outcome.…”
Section: Step 3: Understanding Variation In D Suzukii–parasitoid Intmentioning
confidence: 99%
“…Throughout the course of the invasion of D. suzukii , its genetic diversity changed through bottlenecks and admixture events (Fraimout et al., ). A comparison of the host genotype across neutral markers (6–28 microsatellites) and six X‐linked loci in coding and noncoding sequences indicated relatively high intraspecific genetic variation within and between populations in the invaded regions (Adrion et al., ; Bahder, Bahder, Hamby, Walsh, & Zalom, ; Fraimout et al., , ). It is therefore reasonable to assume that there is substantial intraspecific genotypic variation in the invaded populations that can contribute to the variable D. suzukii –parasitoid outcome.…”
Section: Step 3: Understanding Variation In D Suzukii–parasitoid Intmentioning
confidence: 99%
“…Bahder et al in particular analysed samples of D. suzukii populations collected in California and Washington and determined that while D. suzukii in the former region had high levels of genetic variation, the latter was highly monomorphic [ 22 ]. Furthermore, Fraimout’s group investigated Hawaiian and Spanish populations by exploiting microsatellite markers, finding a significant level of genetic differentiation [ 23 ]. Although both studies exploited two different sets of microsatellites and tested different populations, the authors were led to similar conclusions: they demonstrated the presence of a specific differentiation process among ancestral and derived populations and suggested that for D. suzukii a genetic analysis approach is valuable not only to better understanding of the evolutionary history of the species, but also to manage its great potential for invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account this aspect, we used a population genetic approach to characterise genetic diversity among D. suzukii individuals collected in different regions of Italy. In order to perform this work a set of 15 microsatellites validated by Fraimout and colleagues [ 23 ] were employed. The current research is the first study that provides new insights on the trend of genetic diversity in Italian populations of D. suzukii .…”
Section: Introductionmentioning
confidence: 99%
“…The European and Mediterranean Plant Protection Organization (EPPO) has listed Drosophila suzukii on its A2 List and recently added two new drosophilid species, Zaprionus indianus Gupta and Zaprionus tuberculatus Malloch, on its Alert List (EPPO, 2016a). For D. suzukii, the study of microsatellite markers suggests that European populations come from both Asiatic and North American populations (Fraimout et al, 2015(Fraimout et al, , 2017, but the pathways of introduction are still unknown. The sources of introduction in Europe of these three species are unknown, as are their origins.…”
Section: Introductionmentioning
confidence: 99%
“…The sources of introduction in Europe of these three species are unknown, as are their origins. For D. suzukii, the study of microsatellite markers suggests that European populations come from both Asiatic and North American populations (Fraimout et al, 2015(Fraimout et al, , 2017, but the pathways of introduction are still unknown.…”
Section: Introductionmentioning
confidence: 99%